Financial Report Analysis to Measure the Financial Performance of the South Labuhanbatu Regional Government - Mutiara Aulya Almy; Ayu Kurnia Sari; Vina Arnita (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
This study aims to assess the financial performance of the Labuhanbatu Selatan Regency Government using the fiscal independence ratio, effectiveness ratio, and efficiency ratio during the 2020–2024 period. A descriptive quantitative method was applied, utilizing secondary data obtained from the Local Government Budget Realization Report (APBD). The results indicate that the average fiscal independence ratio remained very low throughout the period, although a significant increase occurred in 2024, shifting the category to high independence. The effectiveness ratio of locally generated revenue (PAD) averaged 95.65%, indicating consistent achievement of revenue targets. However, the efficiency ratio reached an average of 376.83%, suggesting that expenditure management was not optimal. Overall, the findings highlight the need to strengthen fiscal independence, improve the consistency of PAD effectiveness, and enhance budget efficiency in future financial management.